Degradasi Zat Warna Tekstil (Rhodamin B) Dengan Teknologi Aop (Advanced Oxidation Process) Metode Fotokatalitik Menggunakan Katalis Nanokomposit Znfe2o4/SBE - Affananda Taufik; Zultiniar Zultiniar; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Dyestuffs which the result of the textile industry are non-biodegradable organic compounds, can cause environmental pollution especially the aquatic environment. One alternative to processing textile waste is to use the photocatalytic. Photocatalytic is a process of combination of catalyst and light. This study aims to synthesize ZnFe2O4 / SBE catalysts with microwave methods and characterization, study the influence of process conditions in degradation and determine the best process conditions in dye degradation. Nanocomposites from ZnFe2O4 / SBE have been successfully synthesized using the microwave method. The catalyst synthesis process is carried out by microwave for 20 minutes and followed by calcination at 500oC for 5 hours. Photocatalytic degradation lasted 120 minutes, stirring speed 350 rpm and volume of 250 ml solution. The variation of ZnFe2O4 / SBE concentration was 1.5 g / L, 1 g / L, 0.5 g / L and 0.25 g / L and the showed the maximum results from the best photocatalytic process obtained from variations in the catalyst concentration of 1.5 g / LKeywords: photocatalytic, rhodamine b, znfe2o4/sbe